OPEN DEFECATION AND HUMAN SECURITY CHALLENGES: ASSESSING THE SITUATION IN BAMAHU, GHANA - Marfo, S.; Badu-Yeboah, K.; Akparep, Y. J. (UDS International Journal of Development, 2019)
A recent report by the United Nations Development Programme indicates that the best approach to global insecurity is to promote human security which includes; economic security, food security, health security and environmental security. Apparently, in Ghana certain practices including open defecation challenge the promotion and achievement of human security, a vital core of all humans. It is against this background, that Bamahu, a University community in the Wa Municipality of Upper West Region of Ghana was purposely selected in a case study designed with the view of exploring the factors influencing the practice of open defecation and how that practice affects human security of the people. A quota sampling technique was employed in selecting 84 respondents. In addition, three (3) key informants were purposely selected. Data gathered through interviews revealed that open defecation is principally influenced by lack of toilet facilities and affects three core areas of human security condition of the people in the study locality namely; economic security (increase in family expenses and halting of economic activities), health security (contraction of diseases) and environmental security (air pollution and bad eyesight) with the worst affected being health security (98%). This paper recommends that stakeholders under Wa Municipal Assembly should ensure that the available public toilets in Bamahu community are hygienically maintained. Besides, student hostel operators and landlord/landladies should be encouraged to construct more toilet facilities in their homes. Keywords: Bamahu, Open Defecation, Economic Security, Environmental Security; Health Security